Assessing the efficacy of nationwide virtual professional development in Indonesia - Tri Wintolo Apoko; Budi Waluyo (Universitas Syiah Kuala, 2025)
This study presents a comprehensive evaluation of a national virtual professional development (VPD) programme in Indonesia, lasting over four months and involving a diverse cohort of teachers. Utilising a sequential explanatory mixed method design within an interpretivist paradigm, it aimed to assess the programmes effectiveness in enhancing in-service EFL teachers pedagogical skills. The participants of this study were 76 in-service EFL teachers attending the Teacher Profession Education Programme (TPEP) over four months at a reputable private university in Jakarta, Indonesia. The study combined quantitative analyses of surveys and test scoresusing descriptive statistics to examine perceptions of the programmes usefulness, content, design, and learning outcomes, and bivariate correlation to assess the relationships with test scoreswith qualitative insights from the written interviews, which were analysed through deductive thematic analysis. Quantitative findings showed a high perceived efficacy of the TPEP (M = 3.96, SD = .55), with high ratings for perceived usefulness (M = 4.00, SD = .69), course content and design (M = 3.98, SD = .72), and learning outcomes (M = 3.91, SD = .55). However, no significant correlations were found between perceived efficacy and test scores (r = .06, p = .60) despite the strong correlations found among the perception variables themselves (e.g., usefulness and design: r = .88, p .001). Qualitative findings echoed these results, highlighting the programmes flexibility, improved pedagogical knowledge, and confidence, alongside issues like inconsistent guidance and technological challenges.